An experimental investigation of ultrasonic anti-fouling technology - Goh, Jun Xian (2015)
Biofilm formation becomes a problem known as bio-fouling when undesirable biofilm growth and its subsequent development occurs on man-made surfaces, inhibiting the functions of such surfaces. This is especially prominent in the marine industry, where bio-fouling happens on the outer hull of vessels and causes increased fuel and maintenance cost as well as loss of income. Anti-fouling is important to reduce the cost to the marine industry in fuel and time. The most common anti-fouling method used by the industry is currently anti-fouling paints but these paints are poisonous to other marine organisms, and ecologically friendly solutions have to be found for the future. Recent research has pointed to the effectiveness of ultrasound in reducing the attachment rate of various microorganisms, leading to the development and sale of ultrasonic anti-fouling solutions for small vessels such as yachts. However, the impact of such systems in solving the fouling problems of the world’s commercial fleet is limited. Shear horizontal guided waves can be applied to make use of the guided wave effect and extend the usefulness of ultrasonic anti-fouling systems to larger vessels. In this experiment, ultrasonic treated steel bars are immersed together with non-treated bars into a glucose solution with a small percentage of Pseudomonas aeruginosa bacteria culture for 60 hours to allow biofilm formation on the steel bars. After 60 hours, the biofilm was removed and quantified. It was determined that experimental results support the hypothesis that application of ultrasonic waves in shear horizontal mode will reduce the attachment rate of bacteria. This experiment is an early step in the development of large scale ultrasonic anti-fouling systems, and more research still needs to be done in the area to study in greater depth the effects of shear horizontal ultrasonic waves on other fouling organisms, to cross confirm the results of this experiment and to address areas in this experiment that need to be improved.